2009
DOI: 10.1016/j.virusres.2009.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Nipah virus fusion protein: Influence of cleavage site mutations on the cleavability by cathepsin L, trypsin and furin

Abstract: Nipah virus (NiV), a highly pathogenic member of the Paramyxoviridae which originated from bats, encodes for a fusion (F) protein which is proteolytically processed within endosomes by cathepsin L. We show here that sequence requirements for NiV F activation differ markedly from other para- or orthomyxoviral fusion proteins. In contrast to other viral fusion proteins with monobasic cleavage sites, processing of NiV F proteins with one single basic amino acid in the cleavage peptide by exogenous trypsin is very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…However, the NiV proteolytic activation pathway differs from that for other systemically replicating paramyxoviruses, for example, measles virus (MV). F proteins of MV are activated by the ubiquitous Golgi apparatus protease furin during transport to the cell surface, resulting in almost complete MV F cleavage (Ͼ95%) (16,38). In contrast, the inactive precursor NiV F 0 is transported to the cell surface and must then undergo clathrin-mediated endocytosis to get in contact with its activating protease in the endolysosomal compartment.…”
Section: Niv F Cleavage Efficiency Varies Between Different Cell Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the NiV proteolytic activation pathway differs from that for other systemically replicating paramyxoviruses, for example, measles virus (MV). F proteins of MV are activated by the ubiquitous Golgi apparatus protease furin during transport to the cell surface, resulting in almost complete MV F cleavage (Ͼ95%) (16,38). In contrast, the inactive precursor NiV F 0 is transported to the cell surface and must then undergo clathrin-mediated endocytosis to get in contact with its activating protease in the endolysosomal compartment.…”
Section: Niv F Cleavage Efficiency Varies Between Different Cell Typesmentioning
confidence: 99%
“…Unlike cleavage of most other paramyxovirus F proteins, NiV F processing depends on the transport of precursor NiV F 0 to the cell surface and subsequent endocytosis mediated by a tyrosine-based internalization signal in its cytoplasmic tail ( 525 YSRL) (18,77). Within the endolysosomal compartment, F 0 is then ubiquitously activated by pH-dependent proteases at its monobasic cleavage site (arginine 109) (16,48). After cleavage and release of the hydrophobic peptide at the N terminus of F 1 , the fusion-active F 1 -F 2 form is recycled to the cell surface, where it can induce syncytium formation or is incorporated into budding virus particles.…”
mentioning
confidence: 99%
“…Some viruses use the protease activity of particular cellular enzymes localized in the endosomes or at the cellular surface for activating their EnvGP. The Ebola filovirus (for which the GP1-GP2 envelope glycoprotein is cleaved by the furine in the producer cells) (Chandran et al, 2005;Schornberg et al, 2006), the HeV (Pager and Dutch, 2005), NiV (Diederich et al, 2009), or the SARS-CoV and MHV-2 coronaviruses (for which the S spikes is not cleaved in the producer cells) (Huang et al, 2006;Qiu et al, 2006;Simmons et al, 2005) require the cysteins lysosomal proteases, the L or B cathepsine (CatL or CatB) for their entry process. After virus uptake following angiotensin-converting enzyme 2 receptor binding, cathepsin L-mediated proteolysis induces conformational changes in the SARS-CoV S glycoprotein to trigger the endosomal membrane fusion process (Simmons et al, 2005).…”
Section: Fusion Activation By Proteasesmentioning
confidence: 99%
“…To test our hypothesis, we used protease inhibitors to identify cathepsin L to be the protease responsible for cleaving the G protein in Vero cells and demonstrated that cleavage likely occurs during endocytic recycling. Others have shown that the Nipah virus fusion protein is activated by cathepsin L during recycling (25,26). In addition, endocytic recycling is important in the envelopment of RSV (27,28).…”
mentioning
confidence: 99%